Metal and Alloy Bonding - An Experimental Analysis Charge Density in Metals and Alloys - Saravanan, R.; Rani, M. Prema; SpringerLink (Online service) (London : Springer London, 2012)
Charge density analysis of materials provides a firm basis for the evaluation of the properties of materials. The design and engineering of a new combination of metals requires a firm knowledge of intermolecular features. Recent advances in technology and high-speed computation have made the crystal X-ray diffraction technique a unique tool for the determination of charge density distribution in molecular crystal. Methods have been developed to make experimental probes capable of unraveling the features of charge densities in the intra- and inter-molecular regions of crystal structures. In Metal and Alloy Bonding - An Experimental Analysis, the structural details of materials are elucidated with the X-ray diffraction technique. Analyses of the charge density and the local and average structure are given to reveal the structural properties of technologically important materials. Readers will gain a new understanding of the local and average structure of existing materials. The electron density, bonding, and charge transfer studies in Metal and Alloy Bonding - An Experimental Analysis contain useful information for researchers in the fields of physics, chemistry, materials science, and metallurgy. The properties described in these studies can contribute to the successful engineering of these technologically important materials.
1. Introduction -- 2. Charge Density Analysis from X-Ray Diffraction -- 3. Results and Discussion -- 4. Conclusion.
Keywords: Materials science; Physical chemistry; Atomic structure; Molecular structure; Spectra; Industrial engineering; Metals; Materials Science; Metallic Materials; Operating Procedures, Materials Treatment; Physical Chemistry; Atomic/Molecular Structure and Spectra; Electronic books